Uma avaliação do nível de evidenciação das companhias abertas, no Brasil, no tocante aos instrumentos financeiros - Jorge Vieira da Costa Junior (Revista Contabilidade & Finanças, 2003)
O propósito deste trabalho é o de levantar o quadro atual da política de evidenciação de instrumentos financeiros por parte das companhias abertas no Brasil, através de suas demonstrações contábeis (data base de 31.12.2000). Uma pesquisa junto a 215 companhias abertas foi levada a efeito visando a avaliar se a divulgação de fatores de risco de mercado e de sua gestão foi feita adequadamente (de forma qualitativa e quantitativa), se as estratégias dispensadas ao uso dos instrumentos financeiros foram adequadamente reveladas, se foram computados e revelados os valores justos dos instrumentos financeiros, enfim, se os ditames da Instrução CVM nº 235/95, de 23.03.95, foram observados rigorosamente pelas companhias abertas. O resultado da pesquisa indicou que as companhias abertas no Brasil, não prestam informações adequadas em suas demonstrações contábeis, no que concerne aos instrumentos financeiros. This paper aimed to investigate the current stage of the disclosure policy of publicly-held companies in Brazil with respect to financial instruments, by means of the analysis of their financial statements (fiscal year ending at December 31st 2000). A research of 215 publicly-held companies was realized in order to evaluate the adequate disclosure (qualitatively and quantitatively speaking) of risk market factors and their management, the adequate revelation of the strategies for using financial instruments, the adequate calculation and revelation of the fair values of the financial instruments, and finally, if the paragraphs of CVM Instruction nº. 235/95, from March 23rd 1995, were strictly observed by the publicly-held companies. Moreover, the role of the independent auditors in this context was evaluated through the analysis of their audit opinions. The research result indicated that the publicly-held companies in Brazil do not render appropriate information about the financial instruments in their financial statements, with the consent of their independent auditors.Part of the responsibility may also be attributed to the Regulator, due to the absence of a more educational and explanatory regulation (of the "how to do" kind).